2004
DOI: 10.5194/angeo-22-1019-2004
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative magnetotail characteristics of different magnetospheric states

Abstract: Abstract. Quantitative relationships allowing one to compute the lobe magnetic field, flaring angle and tail radius, and to evaluate magnetic flux based on solar wind/IMF parameters and spacecraft position are obtained for the middle magnetotail, X=(−15, −35) R E , using 3.5 years of simultaneous Geotail and Wind spacecraft observations. For the first time it was done separately for different states of magnetotail including the substorm onset (SO) epoch, the steady magnetospheric convection (SMC) and quiet per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
69
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 45 publications
(82 citation statements)
references
References 46 publications
9
69
1
3
Order By: Relevance
“…The BTF phase of delayed substorms can thus be viewed as the short-duration and low-AL extension of the SMC-like activity. One more significant quantitative difference is the average tail magnetic flux value during the BTF phase (0.72 GWb), considerably higher than <F SMC > = 0.57 GWb from DeJong et al [2007] and < F SMC > = 0.52 GWb obtained for given solar wind conditions by Shukhtina et al [2004] and shown in Figure 3. Compared to B Z numbers in the latter study the magnetotail configuration during BTF is more stressed compared to regular steady convection events.…”
Section: Discussion/concluding Remarksmentioning
confidence: 60%
See 1 more Smart Citation
“…The BTF phase of delayed substorms can thus be viewed as the short-duration and low-AL extension of the SMC-like activity. One more significant quantitative difference is the average tail magnetic flux value during the BTF phase (0.72 GWb), considerably higher than <F SMC > = 0.57 GWb from DeJong et al [2007] and < F SMC > = 0.52 GWb obtained for given solar wind conditions by Shukhtina et al [2004] and shown in Figure 3. Compared to B Z numbers in the latter study the magnetotail configuration during BTF is more stressed compared to regular steady convection events.…”
Section: Discussion/concluding Remarksmentioning
confidence: 60%
“…For the first group, we selected 33 ideal substorms with monotonous flux increase from the quiet background with ΔF > 0.5 (< F onset > − < F SMC >). The statistical levels < F onset > and < F SMC > just before onset and during the steady magnetospheric convection (SMC) events were obtained by Shukhtina et al [2004] as a function of solar wind parameters. Typically, this threshold value was about 0.2 GWb.…”
Section: Discussionmentioning
confidence: 99%
“…We take advantage of exploiting the extensive data base of the merged solar wind and plasma sheet observations classified by different dynamical states, previously used to obtain the statistical regression models for the lobe magnetic field and tail flaring angle (also the tail radius and magnetic flux) as a function of solar wind parameters (Shukhtina et al, 2004), thereafter referred to as Paper 1. Referring to this paper for further details, we briefly review the data selection criteria.…”
Section: Data Base and Event Selectionmentioning
confidence: 99%
“…As in PR96, the α(x) dependence is taken as sin 2 α = A 2 exp(Cx). According to the statistical study by Shukhtina et al (2004), the average C value is C = 0.0714. All formulas are presented in the geocentric solar magnetospheric (GSM) coordinate system.…”
Section: Introductionmentioning
confidence: 99%